Role of Semaphorins in Angiogenesis and Innervation in Human Intervertebral Disc Degeneration. (May 2014) - Binch, A. LA.; Phillips, K. L; Chiverton, N.; Cole, A.; Michael, A. R.; Breakwell, L.; Cross, A. K.; Le Maitre, C. L.
Introduction: Although the intervertebral disc (IVD) is considered the largest aneural structure within the human body, during degeneration nociceptive nerves are seen to accompany blood vessels into the IVD yet it remains unclear how this process occurs. Semaphorins are axonal guidance molecules known to repulse nerves by altering the actin cytoskeleton of growth cones. Semaphorin 3A (sema3A) has recently been localized in healthy IVDs, suggesting an inhibitory role toward neural and vascular ingrowth. This study aimed to first identify the presence of the class 3 semaphorins and sema4D shown to be involved in promoting angiogenesis and their receptors within nucleus pulposus(NP) cells and an endothelial cell line and determine whether their expression could be altered by cytokine treatment. Materials and Methods: Real-time PCR (RT-PCR) was performed to investigate gene expression of class 3 semaphorins; Sema3A-3F, sema4D, their receptors plexin A1-A4 and plexin D1 and neuropilin-1 (NRP-1) and NRP-2 in directly extracted RNA from human NP cells and NP cells cultured in alginate for 2weeks before treatment for 48hours with interleukin (IL)-1, IL-6, or tumor necrosis factor α(TNFα) at 0 to 100ng/mL. Similarly, HDMEC-1 endothelial cells were treated with IL-1, IL-6, or TNFα at 0 and 10ng/mL for 48hours, after which mRNA expression was investigated by RT-PCR. Results: Expression of semaphorins and their receptors were present in normal and degenerate disc samples. In human NP cells, IL-6 inhibited semaphorin expression, whereas IL-1 and TNFα significantly increased sema3D over 10-fold ( p ≤0.05). IL-1 upregulated all plexins, conversely TNFα significantly decreased plexin A2. NRP-2 showed a significant increase in response to IL-1. While NRP-1 was significantly decreased in response to IL-1. In HDMEC-1 cells IL-1 significantly increased sema3C and sema3D while TNF significantly increased sema3C. TNF significantly increased NRP-2 expression, however, NRP-1 was decreased by all cytokines. Plexin receptor expression was increased upon IL-6 and TNF treatment whereas IL-1 caused significant decrease in plexin A3 expression. Conclusion: Here, we have demonstrated that several cytokines known to be upregulated during disc degeneration and disc prolapse, regulate expression of certain members of class 3 semaphorins, as well as their receptors in human NP cells and HDMEC-1 cells. This data suggests that the presence of these factors within the degenerate disc may be responsible for modulating the ingrowth of blood vessels and promote nerve ingrowth leading to discogenic pain. Disclosure of Interest None declared